2016
DOI: 10.1021/acs.jafc.6b03474
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity-Enhancing Activity of Phlorizin Is Associated with Lipopolysaccharide Decrease and Gut Microbiota Changes in Obese and Type 2 Diabetes (db/db) Mice

Abstract: Phlorizin exists in a number of fruits and foods and exhibits many bioactivities. The mechanism of its antidiabetic effect has been known as it can competitively inhibit sodium-glucose symporters (SGLTs). However, phlorizin has a wide range of two-phase metabolism in systemic circulation and shows poor oral bioavailability. An alternative mechanism may involve gut microbiota in intestine. Sixteen obese mice with type 2 diabetes (db/db) and eight age-matched control mice (db/+) were divided into three groups: d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 69 publications
4
69
1
Order By: Relevance
“…Dihydrochalcones are a specific group of polyphenolic compounds from apples with potential to reduce blood glucose levels [45,46] which is helpful in diabetes prevention. Oral antidiabetic drugs based on phloridzin conjugate were suggested as well [47].…”
Section: Discussionmentioning
confidence: 99%
“…Dihydrochalcones are a specific group of polyphenolic compounds from apples with potential to reduce blood glucose levels [45,46] which is helpful in diabetes prevention. Oral antidiabetic drugs based on phloridzin conjugate were suggested as well [47].…”
Section: Discussionmentioning
confidence: 99%
“…Since its isolation from the bark of the apple tree 180 years ago, it has been used in human medicine for long because of its extensive bioactivities (Barreca, Bellocco, Lagan, Ginestra, & Bisignano, ; Gosch, Halbwirth, & Stich, ; Rezk, Haenen, Van Der Vijgh, & Bast, ; Qin, Xing, Zhou, & Yao, ). Most studies revealed the anti‐diabetic effect of phlorizin (Mei et al, ; Rossetti, Smith, Shulman, Papachristou, & Defronzo, ) and some studies reported its antioxidant (Rezk et al, ) and anti‐inflammatory activities (Huang et al, ). Recently, a study has indicated that phlorizin supplementation attenuates obesity and decreased plasma pro‐inflammatory cytokines levels in high fat diet fed obese mice (Shin, Cho, Jung, Ryu, & Choi, ).…”
Section: Introductionmentioning
confidence: 99%
“…All of the following animal experimental procedures were approved by the animal ethics committee of Chengdu University. According to the literature and the results of previous research [ 46 , 47 ] the intragastric dose of PHZ was 20 mg/kg [body weight (BW)/day], and the dosage of the DIDE was fixed to be 45 mg/kg (BW/day) based on the content of PHZ contained (45% of PHZ in DIDE: 45 mg DIDE containing 20 mg PHZ and 25 mg NP), the intragastric dose of the NP is 25 mg/kg (BW/day). The mice were then randomly divided into 5 groups: (1) normal chow diet group (NCD, 10% energy from fat, n = 10); (2) high-fat diet group (HFD, 45% energy from fat, n = 10); (3) high-fat diet with DIDE groups (HFD + DIDE, 45 mg/kg (BW/day), n = 10); (4) high-fat diet with PHZ groups (HFD + PHZ, 20 mg/kg (BW/day), n = 10); (5) high-fat diet with NP groups (HFD + NP, 25 mg/kg (BW/day), n = 10).…”
Section: Methodsmentioning
confidence: 99%